Chinese: Myths and Reality - Daulet, F. N. (Journal of Oriental Studies, 2016)
The author talks about common myths about the Chinese language and analyzes the genesis of these myths. PRESENTS hieroglyphic, Chinese phonetic system, which are the most difficult parts to study.